2023
DOI: 10.1038/s41467-023-37674-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell dynamics deconvoluted by single-cell RNA sequencing in normothermic machine perfusion of the liver

Abstract: Normothermic machine perfusion (NMP) has emerged as an innovative organ preservation technique. Developing an understanding for the donor organ immune cell composition and its dynamic changes during NMP is essential. We aimed for a comprehensive characterization of immune cell (sub)populations, cell trafficking and cytokine release during liver NMP. Single-cell transcriptome profiling of human donor livers prior to, during NMP and after transplantation shows an abundance of CXC chemokine receptor 1+/2+ (CXCR1+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 98 publications
2
20
1
Order By: Relevance
“…MMP19 has also been implicated in M2 polarization [75], consistent with the anti-inflammatory signatures of the infected macrophage populations ( Figures 4J and S5E ). Cellular interactome analysis further predicted the anti-inflammatory status of neutrophils by a strong correlation in the CCL signaling pathway between neutrophils and M2-like macrophages, particularly through the Ccl3:Ccr1 axis ( Figures 5K-M and S6D ), an interaction predictive of neutrophil extravasation during E. faecalis infection[76]. Neutrophil extravasation is a vital event in immune responses to infections to ensure the survival of the host[7].…”
Section: Resultsmentioning
confidence: 99%
“…MMP19 has also been implicated in M2 polarization [75], consistent with the anti-inflammatory signatures of the infected macrophage populations ( Figures 4J and S5E ). Cellular interactome analysis further predicted the anti-inflammatory status of neutrophils by a strong correlation in the CCL signaling pathway between neutrophils and M2-like macrophages, particularly through the Ccl3:Ccr1 axis ( Figures 5K-M and S6D ), an interaction predictive of neutrophil extravasation during E. faecalis infection[76]. Neutrophil extravasation is a vital event in immune responses to infections to ensure the survival of the host[7].…”
Section: Resultsmentioning
confidence: 99%
“…Single-cell RNA expression studies have revealed significant heterogeneity in the immune cell profiles in liver grafts, providing new therapeutic targets to prevent rejection [31 ▪▪ ]. Similar studies showed that normothermic machine perfusion shifts several immune cell populations in the donor liver [32 ▪▪ ] – inflammatory neutrophils take on an exhausted phenotype while tolerogenic monocytes increase. These shifts likely impact the donor liver's immunogenicity [33 ▪▪ ].…”
Section: The Pieces Of the Omics Puzzle And Their Influence On Liver ...mentioning
confidence: 95%
“…While the protective effect of NMP on ischemia/reperfusion injury occurs mainly when the perfusion is applied instead of conventional cold storage, as described in most initial studies, when combined with higher donor risk, steatosis, warm, or cold, NMP seems to have limited benefit (Figure 1). 9,11,12 The described changes in immunogenicity are, therefore, no surprise and were highlighted recently by the group from Innsbruck. Hautz et al 9 found a large, neutrophil-dominant leukocyte efflux into the perfusate during prolonged NMP.…”
mentioning
confidence: 91%
“… 9,11,12 The described changes in immunogenicity are, therefore, no surprise and were highlighted recently by the group from Innsbruck. Hautz et al 9 found a large, neutrophil-dominant leukocyte efflux into the perfusate during prolonged NMP. Authors further highlight a shift from a proinflammatory state toward a chronically activated and exhausted neutrophil phenotype, contributing to the general inflammatory response observed during NMP.…”
mentioning
confidence: 91%
See 1 more Smart Citation